Enhancing Visual Perception and Motor Accuracy among School Children through a Mindfulness and Compassion Program - Tarrasch, Ricardo; Margalit-Shalom, Lilach; Berger, Rony (Frontiers in Psychology, 2017)
The present study assessed the effects of the mindfulness/compassion cultivating program: “Call to Care-Israel” on the performance in visual perception and motor accuracy, as well as on anxiety levels and self-reported mindfulness among 4th and 5th grade students. One hundred and thirty-eight children participated in the program for 24 weekly sessions, while 78 children served as controls. Repeated measures ANOVA’s yielded significant interactions between time of measurement and group for visual perception, motor accuracy, reported mindfulness and anxiety. Post-hoc tests revealed significant improvements in the 4 aforementioned measures in the experimental group only. In addition, significant correlations were obtained between the improvement in motor accuracy and the reduction in anxiety and the increase in mindfulness. Since visual perception and motor accuracy are basic skills associated with quantifiable academic characteristics, such as reading and mathematical abilities, the results may suggest that mindfulness practice has the ability to improve academic achievements